쌍태임신에서 임신 전 체질량지수 및 임신 중 체중증가에 따른 임신 예후 - 김명주; Myung Joo Kim; 나은덕; Eun Duc Na; 이경진; Kyoung Jin Lee; 차동현; Dong Hyun Cha; 신중식; Joong Sik Shin; 이화영; Hwa Young Lee (Obstetrics & gynecology science, 2012)
목적 2009년 개정된 Institute of Medicine (IOM)의 권고안에 근거하여 쌍태임신 산모의 임신 전 체질량지수(body mass index, BMI) 및 임신 중 체중증가량에 따른 임신 예후를 분석하고자 한다. 연구방법 2008년 1월부터 2010년 12월까지 분만한 쌍태임신 산모 500명 및 쌍태아 1,000명을 대상으로 후향적으로 연구하였다. 산모의 임신 전 BMI에 따라 저체중(BMI＜18.5 kg/m2)군, 정상체중(18.5≤BMII＜23 kg/m2)군, 과체중(23.0≤BMII＜25 kg/m2)군, 비만(BMI≥25 kg/m2)군, IOM의 임신 중 권장 체중증가량에 따라 미달군, 적정군, 초과군으로 나누어 비교 분석하였다. 결과 전체 500명 산모 중 저체중군 76명(15.2%), 정상체중군 330명(66.0%), 과체중군 55명(11.0%), 비만군 39명(7.8%), 미달군 237명(47.4%),적정군 220명(44%), 초과군 43명(8.6%)이었다. 임신 중 총 체중증가량은 평균 16.3±4.9 kg, 주당 체중증가량은 평균 0.45±0.13 kg/wk 였다. 저체중군 및 미달군에서 빈혈, 비만군에서는 임신성 당뇨의 발생 비율이 높았다. 초과군에서는 부당과량아, 임신성 고혈압, 신생아의 5분 Apgar 점수 7점 미만의 발생률이 높게 나타났다. 결론 쌍태임신에서 임신 전 저체중 또는 비만인 경우, 임신 중 체중증가가 적거나 과도한 경우에 불량한 임신 예후와 연관이 높다. 따라서 상담및 교육을 통해 임신 전 정상 체질량지수를 유지하고 임신 중 적절한 체중증가를 이끄는 것이 중요하다. Objective To analyze the pregnancy outcome and prognosis related to prepregnancy body mass index (BMI) and gestational weight gain in twin pregnancies according to the 2009 Institute of Medicine recommendation (IOM). Methods The study subjects were 500 twin pregnant women and their 1,000 babies delivered from January 2008 to December 2010. The women divided in 4 groups according to prepregnancy BMI; underweight (BMI<18.5 kg/m2), normal weight (18.5≤BMI<23 kg/m2), overweight (23.0≤BMI<25 kg/m2), and obese (BMI≥25 kg/m2) and also categorized 3 groups according to gestational weight gain; "poor" if it was below the IOM range for the prepregnancy BMI, "normal" if it was within the range, and "excessive" if it was above the range. Results Among total 500 twin pregnant women, underweight were 76 (15.2%), normal weight 330 (66.0%), overweight 55 (11.0%) and obese 39 (7.8%); "poor" 237 (47.4%), "normal" 220 (44%) and "excessive" 43 (8.6%). The mean total weight gain during pregnancy was 16.3±4.9 kg and mean weight gain per week was 0.45±0.13 kg/wk. Gestational diabetes mellitus was signifi cantly associated with obese women. Anemia was signifi cantly increased in "poor" weight gain group whereas gestational hypertension, large for gestational age and neonatal Apgar score of 5 minutes under 7 were signifi cantly increased in "excessive" weight gain group. Conclusion The adverse pregnancy and neonatal prognosis were associated with abnormal prepregnancy BMI or gestational weight gain in twin pregnancies. It is important to maintain normal prepregnancy BMI and gestational weight gain through appropriate counseling and education.